Husband and Wife Relationship of Tabligh Jama'ah in Ambehta Mohan India and its Implications for Household Harmony from the Perspective of Mubadalah - Fatimah Amayra Kashvi (Journal of Islamic Mubadalah, 2024)
This article reveals the condition of women in Tabligh Jama'ah families where their husbands do Khurûj fī sabīlillah Khurūj. Islamic women in India are still shackled by patriarchal culture, often getting discrimination and injustice in the name of religion. This phenomenon is analyzed from the perspective of mubadalah. The purpose of this article is how is the form of husband and wife relations if the husband does Khurûj fī sabīlillah Khurūj from a mubadalah perspective and its impact on the household? This type of article is qualitative, analyzing in depth related to the relationship between husband and wife Khurûj fī sabīlillah Khurūj, this field research was conducted in Ambehta Mohan Village is a village located in Nanauta Mandal Saharanpur district in Uttar Pradesh, India. Data collection techniques through observation, interviews and documentation. The results of research in Ambehta Mohan Village found that, husband and wife relations in the families of Tabligh Jama'ah who do Khurūj Fī Sabīlillāh in practice the relationship is not balanced, the wife experiences a double workload, the wife does domestic work while earning a living. The practice of Khurūj Fī Sabīlillāh causes household disharmony. Indian women's equality organizations have socialized women's equality programs, but this is not easy because the patriarchal culture and caste classification in Ambehta Mohan Village are still very strong.